The Effect of Yoga Exercises on the Uterine Involution Process in Postpartum Mothers in the Working Area of Wanayasa Health Center, Purwakarta Regency, Indonesia - Hermina, Ine (HM Publisher, 2024)
Uterine involution is the process of the uterus returning to its pre-pregnancy size and weight. This process is influenced by several factors, one of which is physical activity. Yoga exercise is one of the physical activities that postpartum mothers can do. This study aims to determine the effect of yoga exercises on the uterine involution process in postpartum mothers in the work area of the Wanayasa Health Center, Purwakarta Regency, Indonesia. This research uses quantitative methods with a quasi-experimental research design. The research sample was 60 postpartum mothers who were divided into two groups, namely the intervention group (30 people) and the control group (30 people). The intervention group was given yoga exercises for 1 week, while the control group was given no intervention. The results showed that there were significant differences between the intervention group and the control group in the uterine involution process. The average decrease in uterine fundal height (TFU) in the intervention group was 0.27 cm/day, while in the control group, it was 0.67 cm/day. This shows that yoga exercise can speed up the process of uterine involution in postpartum mothers.